A Future-Oriented Perspective and History Teaching Alternative in Globalization Era: the Context of Indonesia - Sukardi, Tanto (EDUCARE, 2009)
ABSTRACT: In the current globalization era, we witness quick changes in all sectors of life, and for the society which is conscious of these changes the mastery of science and technology has become a must. The areas of science and technology chosen are certainly the ones commonly perceived to provide real contribution to the struggle with the changes. With reference to the science of history, the big question which arises is: is the science of history still needed in this globalization era considering most of its objects belong to the past? One of the answers to the question is in order to contextualize the values of history education an alternative in the teaching of history should be generated in the hope that future generation will be aware of the social values for the basis of predicting the future. Hence, learning history means understanding the past for better understanding of the current so that the future can be grabbed much better.KEY WORDS: current globalization, science and technology, science of history, future generation and understanding the past for better understanding of the current.About the Author: Dr. Tanto Sukardi, M.Hum. is a Lecturer at the Department of History Education, Faculty of Education and Teacher Training (FKIP) Muhammadiyah University of Purwokerto (UMP) in Central Java, Indonesia. He can be reached at: tanto_sukardi@yahoo.com Â How to cite this article? Sukardi, Tanto. (2009). âA Future-Oriented Perspective and History Teaching Alternative in Globalization Era: the Context of Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.1(2) February, pp.157-168. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (November 10, 2008); Revised (January 1, 2009); and Published (February 17, 2009).